2008
DOI: 10.1039/b718050k
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic variety in zirconium-catalyzed bond-forming reaction of arsines

Abstract: Triamidoamine-supported zirconium complexes have been demonstrated to catalyze a range of bond-forming events utilizing arsines. Three different mechanisms have been observed in these reactions. In the first mechanism, triamidoamine-supported zirconium complexes of the general type (N3N)ZrX (N3N =N(CH2CH2NSiMe3)33-; X = monoanionic ligand) catalyzed the dehydrogenative dimerization of diphenylarsine. Mechanistic analysis revealed that As-As bond formation proceeds via sigma-bond metathesis steps similar to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 49 publications
(40 reference statements)
3
53
0
Order By: Relevance
“…For these complexes, two mechanism have been identified [107]. In the dehydrocoupling of Ph 2 AsH to (Ph 2 As) 2 , kinetic data supported As-As bond formation via -bond metathesis similar to the dehydrocoupling of phosphines by related catalysts [62].…”
Section: Heavier Pnictogen Dehydrocouplingmentioning
confidence: 94%
“…For these complexes, two mechanism have been identified [107]. In the dehydrocoupling of Ph 2 AsH to (Ph 2 As) 2 , kinetic data supported As-As bond formation via -bond metathesis similar to the dehydrocoupling of phosphines by related catalysts [62].…”
Section: Heavier Pnictogen Dehydrocouplingmentioning
confidence: 94%
“…For these complexes, two mechanism have been identified [55]. In the dehydrocoupling of Ph 2 AsH to (Ph 2 As) 2 , kinetic data supported As-As bond formation via -bond metathesis similar to the dehydrocoupling of phosphines by related catalysts [28].…”
Section: Heavier Pnictogen Dehydrocouplingmentioning
confidence: 94%
“…However, no (CyPH) 2 or (CyP) 4 was observed until all PhPH 2 was consumed. It was found that the methyl complex reacts selectively with an equivalent excess of CyPH 2 and PhPH 2 to exclusively form (N 3 N)ZrPHPh (9), which was structurally characterized [55]. The cyclohexyl derivative, (N 3 N)ZrPHCy [28], is known but was not observed within the limits of detection.…”
Section: F P-p Bond Formationmentioning
confidence: 97%
See 1 more Smart Citation
“…The intrinsic reactivity of rare earth complexes can sometimes promote facile reaction at sp 2 and sp 3 C-H groups that are often considered to be quite inert. The intramolecular activation of C-H bonds generally leads to cyclometalated species that can be relevant to various catalytic transformations [32,33]. These complexes also serve as excellent platforms from which unique bonding and reactivity patterns can be studied [20].…”
Section: C-h Bond Activationmentioning
confidence: 99%